S2 Ethnic Variation in Inflammatory Profile in Tuberculosis. (19th November 2012) - Martineau, AR; Coussens, AK; Nikolayevskyy, V; Elkington, PT; Bothamley, GH; Packe, GE; Darmalingam, M; Drobniewski, FA; Davidson, RN; Milburn, HJ; Baker, LV; Barker, RD; et al.
Abstract : Introduction and objectives: Mycobacterium tuberculosis (MTB) emerged as a pathogen in Africa and has co-evolved with humans following the migration to Europe and Asia some 70, 000 years ago. Distinct phylogenetic lineages of MTB associate with hosts of particular genetic ancestry, both in their regions of origin and in distant cosmopolitan urban settings where human populations of different ancestry intermingle. These different strains induce distinct patterns of cytokine and chemokine secretion ('inflammatory profiles') in human macrophages. Circulating and antigen-stimulated inflammatory profiles might therefore be expected to vary significantly between tuberculosis patients of different ethnic origin. We therefore conducted a study to determine whether such variation exists. Methods: We measured circulating and antigen-stimulated concentrations of 43 soluble inflammatory mediators and 14 haematological parameters in 45 patients of African ancestry and 83 patients of Eurasian ancestry receiving intensive-phase antimicrobial therapy for smear-positive pulmonary tuberculosis in London, UK. Host and bacillary genotypes were also determined. Statistical analyses were performed to compare inflammatory profiles in patients of African vs Eurasian ancestry; to investigate the influence of host and bacillary genotype on inflammatory profile; and to determine immunological correlates of speed of elimination of MTB from sputum. Results: Tuberculosis patients of African vs Eurasian ancestry had similar clinical characteristics, but exhibited distinct inflammatory profiles. Patients of African ancestry had lower neutrophil counts, lower serum concentrations of CCL2, CCL11 and vitamin D binding protein (DBP), and lower antigen-stimulated CCL11 secretion than those of Eurasian ancestry, but higher serum CCL5 concentrations and higher antigen-stimulated interleukin 1 receptor antagonist and IL-12 secretion. These differences did not relate to MTB strain variation between groups, but they did associate with ethnic variation in host DBP genotype. Ethnic differences in inflammatory profile became more marked following initiation of antimicrobial therapy, and immunological correlates of speed of elimination of MTB from the sputum were distinct for patients of African vs. Eurasian ancestry. Conclusions: Our study demonstrates a hitherto unappreciated degree of ethnic heterogeneity in inflammatory profile in tuberculosis patients. Candidate immunodiagnostics and immunological biomarkers of response to antimicrobial therapy should therefore be derived and validated in tuberculosis patients of different ethnic origin.